Obelia geniculata - Calder, Dale R. (Zenodo, 2013)
Obelia geniculata (Linnaeus, 1758) Fig. 16e Sertularia geniculata Linnaeus, 1758: 812. Type locality. UK: Dover. According to Cornelius (1975), Linnaeus (1758) is likely to have established this species based on an illustration of material from Dover, England, by Ellis (1755). Voucher material. Off Fort Pierce, between Capron Shoal and the beach, on Thyroscyphus ramosus , 09.v.1974, SCUBA, two colonies, up to 7 mm high, with one empty gonotheca, coll. D. Biggs and D. Mook, ROMIZ B1073.— Hutchinson Island, Walton Rocks area, 27°20’19”N, 80°13’59”W, on algae, 17.ii.1991, collected manually, one colony, up to 5 mm high, with gonophores, coll. D.R. Calder, ROMIZ B1107.— Fort Pierce Inlet, north jetty, north side, 27°28’24.2”N, 80°17’20.3”W, on Thyroscyphus ramosus , 0.1 m, 15.ii.1991, 20° C, collected manually, two colonies, up to 8 mm high, with gonophores, coll. D.R. Calder, ROMIZ B1115.— Sebastian Inlet, 27°51’43”N, 80°26’47”W, washed ashore on Sargassum , 19.ii.1991, collected manually, one colony, up to 5 mm high, without gonophores, coll. D.R. Calder, ROMIZ B1119. Remarks. While often thought to be virtually cosmopolitan in shallow waters, molecular studies (Govindarajan et al . 2005) suggest the existence of cryptic species in hydroids of the Obelia geniculata (Linnaeus, 1758) morphotype. Moreover, the reported latitudinal distribution of O. geniculata , from the subarctic to the tropics, also appears to be exceptionally wide for a single species. Within that geographic range, local morphological variants have been noted. In one example, populations from Chesapeake Bay lack the usual asymmetrical development of perisarc on internodes of the hydrocaulus (Calder 1971), considered characteristic of the species (Cornelius 1995b). Hydroids from Florida examined here had the typical asymmetric thickening of perisarc on stem internodes beneath the distal hydrotheca on each, but colonies appeared to be stunted compared with those from boreal waters of the western and eastern North Atlantic (Calder 1975, 2012). ...